Pengaruh Pelatihan Kerja dan Pengembangan Karir terhadap Kinerja Karyawan di Bank Mandiri Cabang Cikarang - Rifqi Ramadhan; Achmad Fauzi; Novita Wahyu Setyawati (Journal Economic Excellence Ibnu Sina, 2024)
The development of a business institution or company is inseparable from the role of labor (employees). Employees as a unit of human resources (HR) are so important in companies or agencies and as assets that determine the success of an organization when meeting increasingly fierce competitors. Basically, a company is a form of cooperation between two or more individuals, both organizations and groups, which aims to achieve certain goals. In order for the company to be able to continue operating, the company needs to be able to carry out optimization of the resources it has in order to achieve these goals. Therefore, companies must pay attention to and elevate employee performance in order to achieve their goals.